Pemanfaatan Media Audiovisual dalam Pengenalan Kuliner Batak Toba: Studi Pengembangan Materi Ajar BIPA - Syahfitri, Dian; Fajar, Muhammad; Manalu, Okto Dewi Sartika (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2024)
This study aims to identify the effectiveness of using audiovisual media in introducing Batak Toba cuisine in Bahasa Indonesia for Foreign Speakers (BIPA) learning. Audiovisual media was chosen for its ability to present content in a more engaging and contextual manner, which can enhance learner engagement in the learning process. Through a questionnaire given to certified BIPA instructors, this study evaluates various aspects of audiovisual media usage, including media utilization, concept understanding, instructor skills, and the appropriateness of the material presented. The results show that audiovisual media based on Batak Toba cuisine is effective in introducing vocabulary and Indonesian culture, but challenges remain regarding material appropriateness and a deeper understanding of concepts. This research is expected to serve as a foundation for developing more culturally-based and innovative BIPA teaching materials to improve the quality of BIPA learning in the future.